Autophagy regulation depends on ER homeostasis controlled by lipid droplets. Issue 8 (2nd August 2016) - Velázquez, Ariadna P.; Graef, Martin
ABSTRACT: Macroautophagy (hereafter autophagy) is a highly conserved homeostasis and quality control process critically linked to neurodegeneration, metabolic diseases, cancer, and aging. A key feature of autophagy is the de novo formation of autophagosomes, double-membrane vesicular structures encapsulating cytoplasmic cargo for vacuolar turnover and recycling. The membrane rearrangements underlying nucleation, expansion, closure, and vacuolar fusion of autophagosomes are driven by multicomponent core autophagy machinery in cooperation with numerous factors involved in a variety of cellular processes. Our current understanding of the origin and contribution of diverse membrane sources to autophagosome biogenesis and of cellular functions enabling stress-appropriate autophagy responses critical for cell health and survival remains limited. Here, we summarize and discuss our recent findings analyzing the role of lipid droplets (LDs), conserved intracellular storage compartments for neutral lipids, for autophagy regulation. Our data indicate that LDs are dispensable as membrane sources, but fulfill critical functions for maintaining endoplasmic reticulum (ER) homeostasis, including buffering of newly synthesized fatty acids and maintenance of phospholipid composition, required for intact autophagy regulation and cell survival during nutrient stress.